2020
DOI: 10.4162/nrp.2020.14.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of fermentedPlatycodon grandiflorumextract through NF-κB signaling in RAW 264.7 cells

Abstract: BACKGROUND/OBJECTIVES: Platycodon grandiflorum (PG), an oriental herbal medicine, has been known to improve liver function, and has both anti-inflammatory and antimicrobial properties. However, little is known about the immune-enhancing effects of PG and its mechanism. In this study, we aimed to investigate whether fermented PG extract (FPGE), which has increased platycodin D content, activates the immune response in a murine macrophage cell line, RAW 264.7. MATERIALS/METHODS: Cell viability was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Overall, the TLR4/MyD88/NF-κB signaling pathway has attracted widespread attention in the scientific community due to their implant-related innate immune recognition and immuno-modulation [ 50 , 51 ]. In this study, it was found that LPS activated NF-κB signaling pathway and induced inflammation, as the previous study also found [ 52 ]. Meanwhile, in response to cell exposure of the prepared CH and modifiers, the cells showed regulated expression in these assessed proteins involved in the NF-κB signaling pathway, together with an inhibited nuclear translocation of p65 protein.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, the TLR4/MyD88/NF-κB signaling pathway has attracted widespread attention in the scientific community due to their implant-related innate immune recognition and immuno-modulation [ 50 , 51 ]. In this study, it was found that LPS activated NF-κB signaling pathway and induced inflammation, as the previous study also found [ 52 ]. Meanwhile, in response to cell exposure of the prepared CH and modifiers, the cells showed regulated expression in these assessed proteins involved in the NF-κB signaling pathway, together with an inhibited nuclear translocation of p65 protein.…”
Section: Discussionsupporting
confidence: 82%
“…31 In addition, Park and Lee used Saccharomyces cerevisiae to ferment the PG extract, and the platycodin D content increased by 4 times that of the unfermented group. 32 The difference among these studies might be due to the diversity of microorganisms and fermentation methods.…”
Section: Paper Food and Functionmentioning
confidence: 99%
“…The results of the present study demonstrated that the protein expression levels of p-NF-κB were significantly increased in TGF-β1-induced MRC-5 cells, which was consistent with previous studies ( 45 , 46 ). Notably, PG or PG-derived components increase AMP-activated protein kinase (AMPK) signaling in numerous types of cell, such as macrophages and lung carcinoma cells, hepatocellular carcinoma cells ( 47 49 ). Moreover, AMPK activation relieves the inflammatory response via suppression of NF-κB activation and downregulation of IL-1β ( 50 ).…”
Section: Discussionmentioning
confidence: 99%